2006
DOI: 10.1061/(asce)0733-9372(2006)132:11(1422)
|View full text |Cite
|
Sign up to set email alerts
|

Procedure to Quantify Biofilm Activity on Carriers Used in Wastewater Treatment Systems

Abstract: A procedure is presented for evaluating and comparing the biological activity of biofilms attached to various biofilrn caniers by measurement of the glucose consumption rate. 1111S technique allows for the economical design and selection of small particulate biofilm carriers that will maximize substrate removal when used in industrial-scale fluidized bioreactors. Methods for ensuring reproducible results are described. To support the glucose consumption rate findings, biofilm dty weights were obtained at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is also possible that the microorganisms responsible for wastewater treatment were better able to attach onto, and populate, the biofilm media of the BioCord system. Bolton et al (2006) found that media surface properties, such as surface roughness and specific surface area, can strongly influence the accumulation and activity of a biofilm. Therefore, the inherent differences in the composition and surface of each of the attachment media could have contributed to how quickly and firmly microorganisms were able to attach onto the media and form a biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the microorganisms responsible for wastewater treatment were better able to attach onto, and populate, the biofilm media of the BioCord system. Bolton et al (2006) found that media surface properties, such as surface roughness and specific surface area, can strongly influence the accumulation and activity of a biofilm. Therefore, the inherent differences in the composition and surface of each of the attachment media could have contributed to how quickly and firmly microorganisms were able to attach onto the media and form a biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…As such, a lower treatment performance would be anticipated because 'pseudo steady state' microbial growth conditions had not yet been achieved. Based on literature involving similar biofilm treatment technologies, it was estimated that a four-week period would be required for the biofilm treatment technologies to reach their maximum growth phase and pseudo-steady state conditions (Bolton et al, 2006;Lindfors, 2010;.…”
Section: Nitrogen Species and Total Nitrogen Removalsmentioning
confidence: 99%
“…Upflow Sludge Blanket, Biofilm Fluidized Bed, Internal Circulation reactors) have gained considerable interest in the past two decades to meet more stringent regulations, due to high biomass retention time, compactness, and high volumetric conversion rates (Nicolella et al, 2000;Bolton et al, 2006). A new liquid-solid circulating fluidized bed (LSCFB) bioreactor has been developed by Nakhla and his coworkers Cui et al, 2004, Patel et al, 2006, Chowdhury et al, 2008 for biological nutrient removal (BNR).…”
Section: Introductionmentioning
confidence: 99%
“…Applications of different types of particulate biofilm reactors (for example, upflow sludge blanket, biofilm fluidized bed, internal circulation reactors) to meet more stringent regulations have gained considerable interest in the past two decades (Bolton et al, 2006). In these reactors, biofilm typically forms a spherical, compact layer over the particles, which enables attainment of large biofilm surface area and high reactor biomass concentrations (Nicolella et al, 2000).…”
Section: Introductionmentioning
confidence: 99%